The prevalence of CYP2C19 mutations in Turkish patients with dyspepsia - Altay ÇELEBİ and Orhan Kocaman and Hakan SAVLI and Cem AYGÜN and Buğra Tolga KONDUK and Ömer ŞENTÜRK and Sadettin HÜLAGÜ (Turkish Journal of Gastroenterology, 2019)
-